2015
DOI: 10.32607/20758251-2015-7-4-34-45
|View full text |Cite
|
Sign up to set email alerts
|

Study of Functional and Allosteric Sites in Protein Superfamilies

Abstract: The interaction of proteins (enzymes) with a variety of low-molecular-weight compounds, as well as protein-protein interactions, is the most important factor in the regulation of their functional properties. To date, research effort has routinely focused on studying ligand binding to the functional sites of proteins (active sites of enzymes), whereas the molecular mechanisms of allosteric regulation, as well as binding to other pockets and cavities in protein structures, remained poorly understood. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 92 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…In other words, there is more selective pressure on the active site and hence more severe penalties in terms of fitness lost due to mutations on the active site. However, allosteric sites are organism specific and, to the best of our knowledge, are almost unknown in EcDHFR indicating that they may be either dispensable or are under less evolutionary pressure and hence, likely to be more mutable.…”
Section: Combinatorial Therapy: Targeting Allosteric and Active Sitesmentioning
confidence: 97%
“…In other words, there is more selective pressure on the active site and hence more severe penalties in terms of fitness lost due to mutations on the active site. However, allosteric sites are organism specific and, to the best of our knowledge, are almost unknown in EcDHFR indicating that they may be either dispensable or are under less evolutionary pressure and hence, likely to be more mutable.…”
Section: Combinatorial Therapy: Targeting Allosteric and Active Sitesmentioning
confidence: 97%
“…However, discovering allosteric sites that have a dominant effect on protein conformation and respective compounds that modulate these sites is far more challenging than orthosteric drug discovery ( Lu et al, 2019 ; Amamuddy et al, 2020 ). As in many cases, the location of allosteric sites is often unknown and their effects on the intrinsic motion of the protein are difficult to determine experimentally ( Suplatov and Švedas, 2015 ). Our recent review article proposes a number of integrated computational approaches to identify allosteric sites ( Amamuddy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear that allostery is not an exclusive property of sophisticated multi-subunit complexes, but rather a widespread phenomenon that plays a key role in the regulation of many biological processes [4-8]. Computational biology methods were applied to study allostery in an attempt to understand the relationship between function and regulation [6, 9]. Bioinformatic analysis showed that the amino acid sequence of regulatory sites is less conserved and more variable compared to that in catalytic sites [10].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of correlated substitutions in the amino acid sequences of topologically independent but functionally coupled sites on the surface of evolutionary related proteins is increasingly being used to study the molecular mechanisms of allostery [9, 14]. It was shown that such correlating/co-evolving positions can form a network of interacting residues located between the catalytic and regulatory sites in a protein structure, which provides communication between them due to the sequential conformational changes initiated by the binding of a regulatory agent [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation